Government spending, growth and poverty: an analysis of interlinkages in rural India - Fan, Shenggen; Hazell, Peter B. R.; Thorat, Sukhadeo (International Food Policy Research Institute, 1998)
Poverty in rural India has declined substantially in recent decades. This steady decline in poverty was strongly associated with agricultural growth, particularly the green revolution, which in turn was a response to massive public investments in agriculture and rural infrastructure. Public investment in rural areas has also benefitted the poor through its impact on the growth of the rural non-farm economy, and government expenditure on rural poverty and employment programs,which has grown rapidly, has directly benefitted the rural poor. The primary purpose of this study is to investigate the causes of the decline in rural poverty in India, and particularly to disentangle the specific role that government investments have played. We seek to quantify the effectiveness of different types of government expenditures in contributing to poverty alleviation. The study uses state level data for 1970 to 1993 to estimate an econometric model that permits calculation of the number of poor people raised above the poverty line for each additional million rupees spent on different expenditure items. The model is also structured to enable identification of the different channels through which different types of government expenditures impact on the poor. But targeting government expenditures simply to reduce poverty is not sufficient. Government expenditures also need to stimulate economic growth. The model is therefore formulated so as to measure the growth as well as the poverty impact of different items of government expenditure. The results from our model show that government spending on productivity enhancing investments, such as agricultural R&D and irrigation, rural infrastructure (including roads and electricity), and rural development targeted directly on the rural poor, have all contributed to reductions in rural poverty, and most have also contributed to growth in agricultural productivity.